Association between Apnea of Prematurity and Respiratory Distress Syndrome in Late Preterm Infants: An Observational Study - Olivier, François; Nadeau, Sophie; Caouette, Georges; Piedboeuf, Bruno (Frontiers in Pediatrics, 2016)
Abstract Late preterm infants (34 to 36 weeks’ gestation) remain a population at risk for apnea of prematurity (AOP). As infants affected by respiratory distress syndrome (RDS) have immature lungs, they might also have immature control of breathing. Our hypothesis is that an association exists between RDS and AOP in late preterm infants. Objective The primary objective of this study was to assess the association between RDS and AOP in late preterm infants. The secondary objective was to evaluate if an association exists between apparent RDS severity and AOP. Methods This retrospective observational study was realized in a tertiary care center between January 2009 and December 2011. Data from late preterm infants who presented an uncomplicated perinatal evolution, excepted for RDS, were reviewed. Information related to AOP and RDS were collected using the medical record. Odds ratios were calculated using a binary logistic regression adjusted for GA and sex. Results Among the 982 included infants 85 (8,6%) had an RDS diagnosis, 281 (28,6%) had AOP diagnosis and 107 (10,9%) were treated with caffeine for AOP. There was a significant association between AOP treated with caffeine and RDS for all infants (OR = 3.3, 95% CI : 2.0 – 5.7). There was no association between AOP and RDS in 34 weeks infants [AOR : 1.6 (95% CI: 0.7 – 3.8)] but an association remains for 35 [AOR : 5.7 (95% CI: 2.5 – 13.4)] and 36 [OR: 7.8 (95% CI: 3.2 – 19.4)] weeks infants. No association was found between apparent RDS severity and AOP regarding mean oxygen administration duration or complications associated with RDS. Conclusion The association between RDS and AOP in late preterm infants reflects that patients affected by RDS are not only presenting lung immaturity, but also respiratory control immaturity. Special consideration should be given before discontinuing monitoring after RDS resolution in those patients.